Characterisation of nanostructures via terahertz spectroscopy - Parkinson, P; Joyce, H; Xu, X; Gao, Q; Tan, H; Jagadish, C; Herz, L; Johnston, M (2010)
We have used terahertz spectroscopy to measure the conductivity and time-resolved photoconductivity of a range of semiconducting nanostructures. This article focuses on our recent terahertz conductivity studies on semiconductor nanowires and single walled carbon nanotubes. © 2010 IEEE.